A study to identify the factor that causes project delay in construction at Terengganu - Nurul Syakirah, Mohd Ali (2016)
This survey was conducted to find the factors causing time overrun (delay) from the contractor perspective. The objective of this study was to identify the factors and in order to rank the most influence factor. Sets of questionnaires were developed and data was collected by hand distributed and email. The scope of study focused on the construction project in Terengganu. The respondent of this study obtain from contractors registered under G7 with CIDB. The result of this study showed that the higher rate in delay come from external factor. External factor consist three subjects such as weather condition, natural disaster and unavoidable disaster.